CALCULATION OF ACTUAL MODIFICATION OF CYCLOIDAL GEAR BASED ON OPTIMAL APPROXIMATION PRINCIPLE - ZHOU JingYuan; LI TianXing; SU JianXin; WANG Bin; ZHANG RuiYao (Jixie qiangdu)
The amount of cycloidal gear modification is an important factor affecting the evaluation of machining error. At present, a method is proposed to invert the actual modification for a cycloid gear designed by using a composite modification method, where the modification is unknown. By analyzing the composite profiling method for cycloidal gear, the best approximation modification calculation model is constructed with the sum of squared normal errors as the target. And this model is solved by using the modified Powell method to obtain the actual modification parameters of the cycloidal gear. The feasibility ofthis method is verified by measuring the tooth profile of the actual machined cycloidal gear, providing a new way to evaluate the error of cycloidal gear in the case of unknown modification parameters.